UNIVERSAL STATISTICS OF ENERGY LEVELS AT THE METAL-INSULATOR TRANSITION - Zharekeshev, Isa Kh. (Recent Contributions to Physics, 2009)
The nearest-neighbor level spacing distribution is numerically investigated by direct diagonalizing a disordered Anderson Hamiltonians for quantum systems. The level statistics scaling is examined near the metal-insulator transition and the correlation exponent is found. We suggest a new universal level spacing distribution at the critical point of the transition, which is related to the multifractality of the electron wavefunctions.